Mechanisms of radical generation in the removal of phenol derivatives and pigments using different Fe-based catalytic systems - Magario, Ivana (2012)
Phenolic compounds removal is a very active research field due to occurrence and the toxicity of phenolic pollutants in industrial wastewaters. In order to make an a priori selection of the most efficient removal process for a target structure this contribution reviews and compares some of the mechanistic aspects of the oxidation in the presence of hydrogen peroxide and catalyzed by complexed iron which is the in-common element in Fenton systems, plant peroxidases and biomimetics. Different substrates were considered from the most basic phenol molecule to complex structures such as phenolic dyes and lignins. The reactivity of iron is related to its microenvironment generated by ligands and their electron withdrawing capacity thus conditioning the type of cleavage induced on hydrogen peroxide and the oxidation state change on iron upon reaction. The relative concentrations of organic to inorganic free radicals generated control the main catalytic action; i.e. from degradation up to mineralization in Fenton systems or oligomerization up to polymerization in plant peroxidases systems. Moreover, some reaction conditions as the peroxide concentration, the initial molar ratio of organic compounds to peroxide and the type of reaction solvent are identified as key factors to promote a desired action mechanism by peroxidases (and their biomimetics).